قراءة إنمائية استشرافية للدور الجديد للجامعة الجزائرية New role of the Algerian University: a future vision - Nasser, Youcef; Choutri, Amel (University Mohamed Khider of Biskra, Algeria, 2017)
يستعرض هذا البحث الدور الجديد للجامعة (الوظيقة الثالثة) بغرض استكشاف العلاقة بين الجامعة والتنمية؛ حيث استُهِلَّ بتقديم تعريف للوظيفة الثالثة للجامعة في عصر العولمة والطفرة التكنولوجية، كما استُصحِب بالتطرُّق إلى الأسباب التي قد تشكِّل عقبة كأْداء أمام أداء الجامعة الجزائرية لوظيفتها الإنمائية بشكل سلس يستجيب لطموحات الباحثين من ذوي المواهب العالية. يقف البحث، أيضًاً، على القيمة المضافة المتوقَّعة من الدور الجديد للجامعة، ويقدِّم قراءة إنمائية استشرافية لما يمكن أن تضطلع به الجامعة الجزائرية من دور جديد في ظل الاستفادة من تجارب الناجحين. This paper presents the new role of the university (The third function) in order to discover the new relationship between university and development. It starts by defining the third function of university in globalization area and the technological spurt. Then it discusses the obstacles that hamper university to perform, smoothly, its developmental function which must responds to the ambitions of high qualified researchers. This paper addresses also, the subject of the added value expected from the new role of the university, and gives a forward looking and developmental reading about this new role intended from the Algerian university in the light of the successful experiences.